2022
DOI: 10.3233/faia220180
|View full text |Cite
|
Sign up to set email alerts
|

The Skeptic Web Service: Utilising Argument Technologies for Reason-Checking

Abstract: Skeptic is a web service aimed at automatically providing pointers for the critical assessment of a persuasive text. That is, with a natural language text as input, the web service returns a ranked list of questions designed to help readers reason-check fake news and other contentious texts. Internally, Skeptic maps argumentative features of the text to methods for critical assessment, such as the critical questions of argument schemes, ways of evaluating different types of propositions, and signs of possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Such patterns have been created mainly for the argument from consequence scheme. Visser et al (2018) analyze TV political debates on the US 2016 presidential election. This dataset had already been annotated with IAT (to be discussed later), but in this work, the authors have followed two additional theories to annotate the inference relations identified: Walton's argumentation schemes and Wagemans' Periodic Table of Arguments.…”
Section: Walton's Argumentation Schemes Annotationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such patterns have been created mainly for the argument from consequence scheme. Visser et al (2018) analyze TV political debates on the US 2016 presidential election. This dataset had already been annotated with IAT (to be discussed later), but in this work, the authors have followed two additional theories to annotate the inference relations identified: Walton's argumentation schemes and Wagemans' Periodic Table of Arguments.…”
Section: Walton's Argumentation Schemes Annotationsmentioning
confidence: 99%
“…We are aware of a single annotation project making use of the Periodic Table of Arguments model. As mentioned earlier, Visser et al (2018) analyze TV political debates on the US 2016 presidential election. They do so by extending the original IAT-based inference relation annotations with Walton's argumentation schemes and with Wagemans' model, focusing on the first general election debate between Hilary Clinton and Donald Trump.…”
Section: Periodic Table Of Arguments Annotationsmentioning
confidence: 99%